The blendification system : activating potential by connecting culture, strategy, and execution - Bruder, Daniel M. (New York, NY : Routledge, 2020)
"The Blendification System is the intentional actions taken to activate potential by connecting culture, strategy, and execution. These three components (culture, strategy, and execution) of the organization are broken down and built up in the Blendification System creating a path to realize maximum potential. Think of the impact if your organization's strategy was developed and integrated into the company's operating DNA creating the foundation for an energizing, engaging, and inspiring culture. The Blendification System is based on the belief that our human potential is more substantial and meaningful than we presently comprehend. Collectively, an organization's potential is exponentially greater than the level at which most are operating today. Unfortunately, workplace organizations have been stuck in "second gear" and do not embrace and pursue their potential. Companies have been focused on corporate missions that point to market dominance and profit as the foundational motivation. While these mission and vision statements can create a clear organizational focus and align employees, they leave us short of realizing our human and organizational potential. With the Blendification System, employees' work becomes strategically significant creating the motivation to execute on meaningful outcomes that become intertwined in the fabric of the company building and reinforcing an exceptional culture. Because workplace organizations influence and impact employees' personal lives, the company then becomes the catalyst for growth for employees, customers, and communities. The Blendification System is not a theory-based book or a book full of philosophical concepts. The only theory in this book (which is also supported by research) is that we can accomplish much more in our lives than we are accomplishing today"--
"A Productivity Press Book"--Title page.
OCLC-licensed vendor bibliographic record.
Keywords: Corporate culture; Organizational behavior; Strategic planning; Organizational change